2006
DOI: 10.1038/nsmb1085
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the chemotaxis receptor–kinase assembly

Abstract: In bacterial chemotaxis, an assembly of transmembrane receptors, the CheA histidine kinase and the adaptor protein CheW processes environmental stimuli to regulate motility. The structure of a Thermotoga maritima receptor cytoplasmic domain defines CheA interaction regions and metal ion-coordinating charge centers that undergo chemical modification to tune receptor response. Dimeric CheA-CheW, defined by crystallography and pulsed ESR, positions two CheWs to form a cleft that is lined with residues important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
367
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(397 citation statements)
references
References 51 publications
25
367
4
1
Order By: Relevance
“…The models share both similarities and differences with recently proposed alternative models based on crystallographic and EPR data (55). Most of the disagreements among the models arise from different assumptions about the relative spatial positions of CheA domains P3, P4, and P5, emphasizing the sensitivity of current models to interdomain geometries that remain undetermined for the assembled core complex.…”
Section: New Working Models For the Architecture Of The Core Complexmentioning
confidence: 79%
“…The models share both similarities and differences with recently proposed alternative models based on crystallographic and EPR data (55). Most of the disagreements among the models arise from different assumptions about the relative spatial positions of CheA domains P3, P4, and P5, emphasizing the sensitivity of current models to interdomain geometries that remain undetermined for the assembled core complex.…”
Section: New Working Models For the Architecture Of The Core Complexmentioning
confidence: 79%
“…Electron microscopic image analysis of particles assembled from a soluble receptor fragment, CheA and CheW also shows trimers, but with significantly altered geometry in which the three dimers are not arranged in a threefold symmetry [36,37]. The hedgerow arrangement in crystals of an archaeal receptor fragment suggests that archaeal CheA and CheW might associate with separated dimers [34]. Whether the structural diversity implied by these in vitro studies occurs in vivo remains an open question.…”
Section: Architecture Of the Receptor-chea-chew Signaling Complexmentioning
confidence: 99%
“…The skewed sets of heptads are well placed to facilitate bending of the four-helix bundle at the hinge. The two available X-ray structures of chemoreceptor cytoplasmic fragments, from two distantly related species, are indeed bent at the position of the glycine hinge [25,34,46], and substitution of larger residues for hinge glycines appears to lock the receptor in the on-or off-state [46]. Finally, in vivo studies of fluorescently-tagged receptors showed that dimers move closer together on repellent stimulation [47] and further apart on attractant binding [48], movements that could depend on bending at the glycine hinge.…”
Section: Chemoreceptor Homodimers: Structurementioning
confidence: 99%
See 2 more Smart Citations